Survival Rate and Lifecycle in Terms of Uncertainty: Review of Companies from Russia and Eastern Europe - KUZMIN, Evgeny A.; GUSEVA, Valentina E. (Journal of Advanced Research in Law and Economics, 2017)
Company’s sustainability to effects of shocks caused by economic crises, risks, and uncertainty largely depends on self-organization competences. Their development in the lifecycle is interrelated to institutional conditions and external uncertainty. It is this issue that this research was expected to explore. The article points out to the development of corporate dynamic capabilities where their survival rate is a main marker. To proceed with the research’s theoretical and methodological background, we have summarized provisions of the lifecycle and redefined the concept of the corporate survival rate and demography. The strategic approach to lifecycle management has been developed together with the proposed typology of demographic events. In the critical review of academic literature, the authors put forward a number of hypotheses that specify a degree of influence for the corporate environment and the role of institutional control on development of self-organizational competences. Based on findings from empirical testing, the authors have found that as far as lifecycles come and go, in terms of uncertainty the corporate survival rate increases, while the institutional environment quality makes an opposite impact.